Special Issue “New Frontiers in Parameterized Complexity and Algorithms”: Foreward by the Guest Editors - Misra, Neeldhara; Rosamond, Frances; Zehavi, Meirav (Algorithms, 2020)
This Special Issue contains eleven articles—surveys and research papers—that represent fresh and ambitious new directions in the area of Parameterized Complexity. They provide ground-breaking research at the frontiers of knowledge, and they contribute to bridging the gap between theory and practice. The scope and impact of the field continues to increase. Promising avenues and new research challenges are highlighted in this Special Issue.